Chromosome spreading of the 5S rDNA clusters in the karyotype of Gymnotus inaequilabiatus (Gymnotiformes: Gymnotidae): insights into the role of the Rex-1 and Rex-3 retrotransposable elements of this process - Lucas Pietro Ferrari Gianini; Ligia Carla Balini; Fernanda Errero Porto; Luciana Andreia Borin-Carvalho; Carlos Alexandre Fernandes (Neotropical Ichthyology)
Abstract Gymnotus inaequilabiatus has been the subject of few studies concerning the organization of its macro- and micro-karyotypic structures. This article aims to enhance the existing cytogenetic data for G. inaequilabiatus from the upper Paraná River basin by documenting its karyotype and other chromosomal characteristics, including ribosomal DNA (rDNA) and the retroelements Rex-1 and Rex-3, which have yet to be described for this genus. The modal diploid number of 2n = 54, distributed in 34m + 18sm +2a for both sexes, was observed. Single nucleolar organizing regions (NORs) were detected on a metacentric chromosome pair (1st) and confirmed by fluorescence in situ hybridization (FISH) with the 18S rDNA probes. Multiple 5S rDNA sites were detected on 31 chromosomes, mainly in the pericentromeric regions. Heterochromatin was detected at centromeric and pericentromeric regions of all chromosomes and interspersed to NORs. The Rex-1 and Rex-3 elements displayed similar dispersion patterns, characterized by small clusters spread throughout the chromosomes in both euchromatic and heterochromatic regions. Besides, the spreading of Rex-1 and Rex-3 signals in adjacencies of the 5S rDNA sites could reflect their role in the dispersion of these regions. The present data are valuable in helping to understand karyotypic evolution in G. inaequilabiatus.